Looking through the Skiascope: Benjamin Ives Gilman and the Invention of the Modern Museum Gallery - Steven Lubar (Panorama, 2017)

(untitled)
Benjamin Ives Gilman invented the skiascope to ensure that museum visitors saw art as he thought best—without distraction. Unfortunately, as far as I was able to determine, no skiascope survives. And so I built one.